Pematahan Dormansi Benih Kebiul (Caesalphinia bonduc L.) dengan Berbagai Metode - Uyatmi, Yesi; Inoriah, Entang; Marwanto, Marwanto (Akta Agrosia, 2016)
Seed of Caesalpinia bonduc L. is difficult to germinate due to the thick and hard seed coat. The research aims to evaluate various methods for breaking dormancy of C. bonduc seed. This study was conducted from December to January 2016 The way to break the dormancy were arranged in Completely Randomized Design. Eleven methods to solve the seed dormancy of C. bonduc were compared. The ways to break the dormancy were soaking in water with different temperatures. The temperatures were 30C for 0 hours, 5 hours, 10 hours, and 15 hours. Other techniques to break the dormancy were soaking in hot water at 10000C for 5 hours, 10 hours, and 15 hours. Warm stratification with 100% air humidity (RH) at 40C for five days, ten days and 15 days also included as treatments. The last method was seed piercing with a needle. The variables observed in this study were germination capacity, germination rate, epicotyl length, plant height, and root length. The results of this study showed that the 11 methods of breaking seed dorman cy significantly affected germination capacity, germination rate, emerging epicotyl, and plant height. Seed piercing classified as the most efficient method as indicated by the value of 100% in germination capacity, 1.43 in germination rate, 13.64 cm in plant height, and 6.16 cm in root length.0